Study on High Efficiency Operation-Conditions of Solid Oxide Fuel Cell and its System Evaluation - TANAKA, KANAKO; YAMADA, KOICHI; YAMAZAKI, AKIHIRO; WEN, CHING-JU (KAGAKU KOGAKU RONBUNSHU, 1998)
A solid oxide fuel cell (SOFC), its module and 1 MW system using CH4 fuel are designed. The performance data of the SOFC system is calculated over a wide range of working temperatures and steam to carbon ratios (S/C). For the calculation, over-potential and electrolyte resistance values at a lower temperature than 1000°C are assumed to be as the same as those actually obtained at 1000°C. The SOFC system was evaluated using measures of cost and energy payback times (CPT, EPT), The calculation results using thermodynamic data showed that the generation efficiency of SOFC increased with the decrease of the working temperature. A lower temperature operation of SOFC shortened the CPT and EPT, because it enabled the application of lower cost materials, the size-reduction of equipment and the improvement of unit fuel consumption for the SOFC system. The lowering of S/C was also important to decrease the CPT and EPT. The evaluation results indicated that operating conditions of S/C =1.0 1.5 and the working temperature lower than 800°C were target values to realize the SOFC system.